Overtraining and fatigue syndrome in elite athletes - Pakravan, A. (International Journal of Wrestling Science, 2019)
Overreaching: Excessive Exercise volume or intensity - reduced sport-specific athletic performance Temporary impairment Supercompensation - Increased performance Functional overreaching Increased training load Short term (days . weeks) Good: Supercompensation Non-functional overreaching Intense training load Long term (weeks . months): 6 weeks . 8 months Other symptoms: psychologic, neurologic, endocrinologic Bad: Symptoms, time out of training Overtraining Syndrome (OTS) Maladaptive response to excessive exercise without sufficient rest Extreme non-functional overreaching? More than 2 months: 2 years . no recovery Severe varied symptoms Bad: symptoms, time out of training, secondary complications, potential career ending